Intra‐articular anaesthesia of the equine stifle improves foot lameness. (27th June 2019) - Radtke, A.; Fortier, L. A.; Regan, S.; Kraus, S.; Delco, M. L.
Summary: Background: Equine diagnostic anaesthesia can be a useful tool in challenging lameness examinations. However, anaesthetics diffuse over time leading to nonspecific desensitisation of periarticular structures. Nerves that convey sensation from the distal limb to the central nervous system pass in close proximity to the caudal stifle joint capsule. Therefore, diffusion of intra‐articular (IA) anaesthetics could cause inadvertent desensitisation of the distal limb resulting in a false diagnosis of stifle lameness. Objectives: To determine if IA stifle anaesthesia can alleviate lameness originating in the distal limb. Study design: Crossover experiment. Methods: Nine horses were fitted with a circumferential hoof clamp to induce a moderate unilateral hindlimb lameness. Intra‐articular stifle anaesthesia was performed and gait was evaluated every 10 min during the 90‐min trial using an inertial sensor system. Push‐off and landing components of the lameness were assessed by measuring the mean inter‐stride difference between the maximum and minimum heights of the pelvis respectively. Differences were compared using a Wilcoxon signed‐rank test. Results: Overall, horses with hoof clamp‐induced foot pain had a reduction in push‐off lameness after IA stifle anaesthesia. The mean change in diffmax at 90 min was −4.3 mm (P = 0.005) for the experimental group vs. −2.3 mm (P = 0.2) for the control group. Lameness decreased over time, with an average improvement of 23% at 30 min, 33% at 60 min and 38% at 90 min. There was high inter‐horse variability; 3/9 horses improved by 50% within 30 min, while 2/9 improved by 30% and 4/9 had minimal (<10%) or no improvement in lameness. Improvement after IA stifle anaesthesia was not related to the severity of baseline lameness (P = 0.3–0.7). Main limitations: Limited clinical applicability of our lameness induction model. Conclusions: Intra‐articular stifle anaesthesia reduces foot lameness in a third of horses by up to 50% within 30 min. Clinically, the results of IA stifle anaesthesia should be considered in the light of these findings before treatment recommendations are made, as additional diagnostics may be required to rule out pain originating in the distal limb.